2021
DOI: 10.1155/2021/5563426
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Accuracy of Different Apex Locators: Propex IQ, Raypex 6, Root ZX, and Apex ID with CBCT and Periapical Radiograph—In Vitro Study

Abstract: Objectives. This study aimed to validate the accuracy of working length (WL) measurements obtained with the newly introduced Propex IQ apex locator and to compare it with the latest generations of other electronic apex locators, CBCT, and conventional periapical radiographs by using the actual WL measurements obtained by using an endodontics microscope as a reference. Materials and Methods. Thirty-five extracted single-rooted human mandibular first premolars with curvatures from 10° to 20° were selected accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…In the present study, the WL was confirmed both radiographically and with apex locators. The accuracy of modern apex locators measurement is undisputable [ 42 , 43 ]. Additionally, WL measurements with an apex locator showed higher accuracy than conventional periapical radiographs [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the WL was confirmed both radiographically and with apex locators. The accuracy of modern apex locators measurement is undisputable [ 42 , 43 ]. Additionally, WL measurements with an apex locator showed higher accuracy than conventional periapical radiographs [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of modern apex locators measurement is undisputable [ 42 , 43 ]. Additionally, WL measurements with an apex locator showed higher accuracy than conventional periapical radiographs [ 43 , 44 ]. However, periapical lesions seemed to influence the measurements with apex locators [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accurate determination of working length is the primary factor for successful endodontic treatment. A recent study found that cone beam CT-based radiographic measurements were the most accurate method for determining the working length, followed by electronic apex locators, which had very close results to cone-beam CT 5 …”
Section: Discussionmentioning
confidence: 98%
“…Many reports have evaluated the accuracy of EALs in apical constriction at 0.5 mm coronal from anatomic apex and the apical foramen 0.0 mm (Akisue et al2014;Khandewal et al 2015;Aguiar et al 2017;Saxena et al 2018;Golvankar et al 2019;Mahmoud et al 2021), but few studies have considered correlation between the distance from the file tip to the anatomical point and electronic apex locators display readings before the number 0.5 or 0.0, and it is unclear how precise the numbers on the display correlate with file position inside the root canal (Haupt et al 2018;Oliveira et al 2019). No study has assessed the RomiApex A-15 measurements between 2.0 and 0.0 number.…”
Section: Discussionmentioning
confidence: 99%
“…Cone-beam computed tomography is an accurate method that should be used for odontometry, only if the dentist already has this exam indicated for other treatments, avoiding unnecessary radiation to the patient (Connert et al 2018;Paterson et. al 2020;Mahmoud et al 2021) Therefore, the simplest and most used method to obtain the location of the apical foramen is the use of electronic apex locators (Melo et al, 2020;Pham 2021).…”
Section: Introductionmentioning
confidence: 99%